(untitled) (Journal of Biomedical Investigation, 2007)
Serial complete blood counts were performed on venous blood of 104 healthy, normal term Nigerian neonates (55 male, 49 females). The mean weight of the neonates was 3465±398¢ in the first 10 days of life. There were significant depressions in the value of total leucocyte count (8.37±2.38x107/L) on day 7-10 compared to values on day 1-3 (10.57±4.10x10°/L) (p<0.01). Similarly, the value of neutrophils (3.09±1.59x10’/L) on days 7-10 was significantly reduced compared to values obtained during days 1-3 (6.77±3.9x109/L) (<0.01). However, elevations of lymphocyte count (4.89±1.80 x109/L), eosinophils counts (0.22±0.20x10 IL) and platelets count (241±50x10/L) on days 7-10 were observed compared to values of lymphocytes count (3.58±1.40 x109/L), eosinophils count (0.12±0.17x109/L) and platelets count (208±48x109/L) on days 1-3 of life (p<0.01 in each case). The haematocrit, monocytes count and basophils count; were not significantly different within the study period (p>0.1). The present study concludes that Healthy normal term Nigerian neonates presents with varying proportions of total and differential white cell and platelets counts within the first 10 days of life. This may have implications for neonatal haematology in our environment.